Dialogues and Historical Reconstruction of the Department of Basic Education (División de Educación Básica) - Cecilia Dobles-Trejos; Luz Emilia Flores-Davis; Pablo Sisfontes-Guilarte (Revista Electrónica Educare)
The present article is aimed at contributing to the historical development of the academic unit in charge of training teachers at Universidad Nacional de Costa Rica (UNA).  In 1983 a group of educators with many dreams and ideas built the bases of what we know today as the Department of Basic Education (División de Educación Básica-DEB), part of the Center for Research and Teaching in Education (Centro de Investigación y Docencia en Educación-CIDE) at Universidad Nacional de Costa Rica.  The DEB inherited the capacity to reflect and make proposals from the Escuela Normal, the institution that took the first steps in training teachers in the country.  In this way, an ongoing process of revision, reflection, and proposals was started full of good ideas and continues to form part of the daily labors of this academic unit. Throughout the history of the DEB, its reflective vision has allowed it to establish its main purpose: searching for innovative proposals to fill the country’s educational needs.  As part of the 30th anniversary, this article is an overview of the history of this academic unit, paying special attention to the social and economic changes occurring during the 1980’s in the country, and how they influenced the current direction of the unit and how it defines its future orientation towards a diversified academic offering and participation in the development of the country as well as the Central American region.  The foregoing is to be established according to the social and economic demands that characterize the XXI century, such as a balance between the classroom and the social context, the influence of technology and the introduction of virtual education, and the consequent expansion of its social pedagogical influence in the current time and space.  This fact is characterized by an educational global and planetary vision that brings new challenges concerning international cooperation, the command of several languages and the chance to extend DEB’s influence beyond its current limits.  The methodology used in this article was the triangulation of evidence obtained from interviews with DEB directors, a sensitization and reflection workshop developed with DEB’s current academic team in order to recover information, as well as the analysis of regulations, curricula and other institutional documents.